2020
DOI: 10.26773/mjssm.200310
|View full text |Cite
|
Sign up to set email alerts
|

Warm-Up Striding Under Load Does Not Improve 5-Km Time Trial Performance in Collegiate Cross-Country Runners

Abstract: Post-activation potentiation has proven to be an effective strategy to enhance performance for many tasks, but little research has been conducted specifically concerning endurance sport performance. This study examined whether 5-km run performance could be improved by completing pre-run strides while wearing a 6.8 kg weighted compression garment (LOAD). A counter-balanced crossover field study design was incorporated with NCAA Division I Cross Country runners (n = 10) during coach-led, official team pre-season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Most studies showed a low risk of bias for carryover effects, whereas three showed a high risk of bias (34,40,48), and four were classified as having some concerns. Regarding the deviations from the intended intervention, some studies were classified with some concerns (9,16,(33)(34)(35)(37)(38)(39)(40)(41)44,45,(47)(48)(49)(50)(51)(52)(53), but most of the PAPE literature showed a low risk of bias in this domain. The studies included in this review were classified as having a low risk of bias for the missing outcome data domain, as only the study by Wittekind and Beneke (33) showed missing data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies showed a low risk of bias for carryover effects, whereas three showed a high risk of bias (34,40,48), and four were classified as having some concerns. Regarding the deviations from the intended intervention, some studies were classified with some concerns (9,16,(33)(34)(35)(37)(38)(39)(40)(41)44,45,(47)(48)(49)(50)(51)(52)(53), but most of the PAPE literature showed a low risk of bias in this domain. The studies included in this review were classified as having a low risk of bias for the missing outcome data domain, as only the study by Wittekind and Beneke (33) showed missing data.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, the most problematic aspect was the methodology to assess performance outcomes, as the massive part of the literature has adopted biased procedures. For example, several studies did not report if assessors were aware of the intervention being received by participants (42), whereas others declared that assessors provided verbal encouragement during exercise tests used to assess endurance performance (2,16,42,43,46,47,49,50,(52)(53)(54)(55)(56)(57)(58). Despite the exercise performance assessment through objective measures such as power, time, etc., is unlikely to carry observer-derived bias, it is highly concerned that verbal incentives have been provided by assessors aware of the interventions received by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…If we take into account the dynamics of its growth, we can say with certainty that it will soon be included in one of the three most prestigious categories within the "Web of Science" database (SCI, SSCI or SCIE) and will receive an impact factor. Very high quality scientific papers by eminent authors, which were published in the first [34, 35, 36, 37, 38, 39, 40, 41, 42, 43, ] and the second edition of the eight volume [44,45,46,47,48,49,50,51,52,53], and also in the first edition of the ninth volume [54,55,56,57,58,59,60,61,62,63,64]are guarantee that it will happen. At the very end, the youngest, but still a journal that has made notable progress is the "Journal of Anthropology of Sport and Physical Education".…”
Section: Discussionmentioning
confidence: 99%
“…Sportski trening kao sastavni dio trenažne tehnologije, omogućavaju transformacione procese pojedinih segmenata antropološkog statusa sportiste i usavršavanje tehničko-taktičkih elemenata, što u krajnjem vodi ka postizanju vrhunskih sportskih dostignuća. Iz ovog veoma važnog segmenta su prikazani sljedeći radovi: "Exponential versus linear tapering in junior elite soccer players: effects on physical match performance according to playing positions" (Krespi, Sporis, & Popovic, 2019), Neuromuscular adaptations after blood flow restriction training combined with nutritional supplementation: A preliminary study" (Chulvi-Medrano et al, 2019), "The Effects of High-Intensity Interval Training on Skeletal Muscle Morphological Changes and Denervation Gene Expression of Aged Rats" (Tayebi, Siahkouhian, Keshavarz, & Yousefi, 2019), "The Association between Relative Age Effect, Goals Scored, Shooting Effectiveness and the Player's Position, and her Team's Final Classification in International Level Women's Youth Handball" (Saavedra, & Saavedra, 2020), "The Effects of A 6-Week Plyometric Training Programme on Sand Versus Wooden Parquet Surfaces on the Physical Performance Parameters of Well-Trained Young Basketball Players" (Ozen, Atar, & Koc, 2020), "The Effect of an In-Season 8-Week Plyometric Training Programme Followed By a Detraining Period on Explosive Skills in Competitive Junior Soccer Players" (Branquinho et al, 2020), "Warm-Up Striding Under Load Does Not Improve 5-Km Time Trial Performance in Collegiate Cross-Country Runners" (O'Neal et al, 2020), "The influence of coaches' instruction on technical actions, tactical behaviour, and external workload in football small-sided games" (Batista et al, 2019), "The important game-related statistics for qualifying next rounds in Euroleague" (Dogan, & Ersoz, 2019) i "Normative Profile of the Efficacy and Way of Execution for the Block in Women's Volleyball from Under-14 to Elite Levels" (Echeverría, Ortega, & Palao, 2020).…”
Section: Total 30mentioning
confidence: 99%